Business Model Canvas: Smart Bottle / Nurul Ashyikin Ramli - Ramli, Nurul Ashyikin (2020)
The business model canvas is a great tool to understand the business model in a simple, structured way. Using this canvas will lead to insights into the customers we serve, what value propositions are offered through which channels, and how our company makes money. The business model canvas is a shared language for defining, visualizing, analyzing and modifying business models. It describes the rationale of how an organization creates, delivers and captures value. Business model canvas is a simple and easy framework to give an overview of the business. It consists of nine building blocks to understand the overall picture of our chosen business. The objective is to create hands on tools that foster understanding, discussion, creativity, and easily can see the idea in one blue print. The Smart Bottle is a new modern innovation created by Smartle Company as a sauce and ketchup container. It is especially suitable for people who want to travel or have a picnic outside their home. The Smart Bottle is very convenient, because it is not brittle like a glass bottle. It is attractive to travellers because it is compact and easy to bring around, unlike the normal sauce in a glass container. The Smart Bottle is a new packaging product that will provide a lot of benefits to its users. This invention is made of a combination of several materials, including glass, several types of plastic, rubber, sponge and many others. The glass was used to protect the sauce for a longer period of time. As the glasses are fragile and easily scattered, customers often do not choose to carry them on their travels or picnics. Thus, this material has become a weaknesses in the food industry. In order to overcome this problem, the Smart Bottle was created with the utmost protection. A sponge was used to protect the glass barrel from being broken. It will increase the confidence of the customer to keep the product in their bag